Rattan in Malaysia : Process and its application in interior / Abd Halim Mohd Afandi - Mohd Afandi, Abd Halim (Faculty of Architecture, Planning and Surveying, 1990)
In the fast developing world of today, rattan has been one of the local material which being used in furniture and furnished industry.But it is sad to say that truly understanding about rattan is still very low compare to other material. In future, these factors would be totally charges and it would be respected move and the flexibility increase. The abrasive resistance of Calamus Manan (Rotan Manau) and plectocomia species where assessed and compared with that of Kempas, a common flooring timber and Rubberwork a material suitable for light traffic flooring. The results showed that both rattan species are weaker(inferior) to Kempas, but about two time superior to Rubberwood. Thus, they could used for prequet flooring under both the light and medium flooring conditions.. The different species of Rattan Cannes (Calamus Species) availble. In the forest of Kodazn District of Karhataka where trid and their growth was observed for a period of twelve years. Their germination, survival percentage, overallgrowth performance, flowering, and dump formation were studied. This study will help in a preliminary understanding of factors that need consideration for rainsing different species of Cannes in the Kodazn and neighbouring Western Ghat forest. It is good that those involved directly in the rattan manufacturing keep in their strenght, ideas, knowledge and do a cut of resarch and testing. ( to FRIM, Federal Research Institute of Malaysia ). It has always been my hope to see that our Rattans continue to prosper and that will be cherished and put into better usage not only in furniture industry. The thesis is therefore dedicated to this end, with the hope that others will benefit from this study.